AI and Gamification: Exploring the Integration of Generative AI in Interactive English Language Learning Apps - S, Kartika (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
The rapid growth of artificial intelligence (AI) is reshaping education by providing innovative tools for enhancing learning experiences. In language education, AI-powered platforms, such as Generative AI, offer dynamic, real-time interactions that improve user engagement and learning outcomes. Despite the growing interest, limited research exists on integrating AI with gamification in language learning apps. This study aims to fill this gap by examining the impact of Generative AI and gamification on English language acquisition. A mixed-methods design was employed, combining quantitative and qualitative data collection approaches. The research utilized pre- and post-surveys, standardized quizzes, and semi-structured interviews to assess user engagement, motivation, and language learning improvements. A sample of 100-150 participants from UIN Raden Intan Lampung's Faculty of Syari'ah was selected to evaluate the AI-enhanced gamified system. The findings revealed a significant increase in user engagement, with a 35% improvement in session duration and a 28% rise in weekly usage frequency. Learning outcomes showed improvements in vocabulary acquisition, grammatical accuracy, and speaking fluency. The AI’s personalized feedback mechanism was highly rated, although some challenges with speech recognition and consistency in AI responses were identified. These results highlight the potential of combining Generative AI with gamification to enhance language learning experiences. The study implies that further refinement of AI features and regular content updates are necessary to sustain user engagement and optimize long-term learning outcomes.